Efficacy of atropine, orthokeratology, and combined atropine with orthokeratology for childhood myopia: A systematic review and network meta-analysis - Hou-Ren Tsai; Jen-Hung Wang; Huei-Kai Huang; Tai-Li Chen; Po-Wei Chen; Cheng-Jen Chiu (Journal of the Formosan Medical Association, 2022)
Background/Purpose: Orthokeratology (Ortho-K), atropine eye drops and combined atropine with Ortho-K are proven to be effective ways to prevent myopic progression in many studies, but there is scarce evidence regarding the comparative efficacy of different dosages of atropine,Ortho-K, and combined atropine with Ortho-K for childhood myopia. Methods: We performed a network meta-analysis (NMA) to assess the relative efficacy of the aforementioned interventions for myopic progression; moreover, we calculated the surface under cumulative ranking area (SUCRA) to determine the relative ranking of treatments. Results: We identified 19 randomized controlled trials (3435 patients). NMA revealed that 0.01%–1% atropine, Ortho-K, and 0.01% atropine combined with Ortho-K inhibited axial elongation (AL) over one year. For refractive change, SUCRA analysis revealed that the hierarchy was high-dose (0.5%–1%), moderate-dose (0.1%–0.25%), and low-dose (0.01%–0.05%) atropine. Regarding AL, SUCRA analysis revealed the following hierarchy: Ortho-K combined with 0.01% atropine, high-dose atropine, moderate-dose atropine, Ortho-K, and low-dose atropine. Conclusion: In conclusion, we found that atropine (0.01%–1%), Ortho-K, and 0.01% atropine combined with Ortho-K could significantly slow down myopia progression. The atropine efficacy followed a dose-related pattern; moreover, Ortho-K and low-dose atropine showed similar efficacy. There was a synergistic effect of using 0.01% atropine combined with Ortho-K, and it showed comparable efficacy to that of high-dose atropine.